2011
DOI: 10.1161/circinterventions.110.958389
|View full text |Cite
|
Sign up to set email alerts
|

Value of Age, Creatinine, and Ejection Fraction (ACEF Score) in Assessing Risk in Patients Undergoing Percutaneous Coronary Interventions in the ‘All-Comers' LEADERS Trial

Abstract: Background-The age, creatinine, and ejection fraction (ACEF) score (age/left ventricular ejection fractionϩ1 if creatinine Ͼ2.0 mg/dL) has been established as an effective predictor of clinical outcomes in patients undergoing elective coronary artery bypass surgery; however, its utility in "all-comer" patients undergoing percutaneous coronary intervention is yet unexplored. Methods and Results-The ACEF score was calculated for 1208 of the 1707 patients enrolled in the LEADERS trial. Post hoc analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 17 publications
11
94
0
3
Order By: Relevance
“…These criteria are intended to be a user-friendly application that will help reduce the variability in clinical practice of the different medical specialists who treat elderly patients with NSTE-ACS, as well as facilitate clinical judgment based on reasonable criteria to assess whether carrying out invasive treatment is not in fact indicated to improve the current or future prospects of the patient in terms of survival and/or quality of life. This is not a score of risk to determine the risk of an invasive treatment [28][29][30], only a consensus regarding in which cases it is justified not to perform invasive treatment in elderly patients with NSTE-ACS despite such treatment being indicated. To develop this consensus criteria, we followed qualitative methodology (surveys, clinical sessions) using a multidisciplinary approach involving emergency physicians, intensivists, cardiologists, internists and geriatricians.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria are intended to be a user-friendly application that will help reduce the variability in clinical practice of the different medical specialists who treat elderly patients with NSTE-ACS, as well as facilitate clinical judgment based on reasonable criteria to assess whether carrying out invasive treatment is not in fact indicated to improve the current or future prospects of the patient in terms of survival and/or quality of life. This is not a score of risk to determine the risk of an invasive treatment [28][29][30], only a consensus regarding in which cases it is justified not to perform invasive treatment in elderly patients with NSTE-ACS despite such treatment being indicated. To develop this consensus criteria, we followed qualitative methodology (surveys, clinical sessions) using a multidisciplinary approach involving emergency physicians, intensivists, cardiologists, internists and geriatricians.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis allowed for the assessment of the predictive ability of the Global Risk: 1) the HosmerLemeshow test for calibration-the assessment of the correctness of the prediction by the risk model, with poor fit indicated by a significant p value (Ͻ0.05); 2) receiver operator curves for discrimination (C-statistic)-the ability of the risk model to appropriately assign the correct risk prediction in patients who have the outcome, ranging from 0.50 (no discrimination) to 1.0 (perfect discrimination); 3) the Brier score-an overall risk model performance measure capturing both discrimination and calibration aspects of the risk model, ranging from 0 to 1, with a lower value (closer to 0) suggestive of a more predictive risk model (34 -36). Comparisons were made with other risk models, namely, the SXscore (2,4); age, creatinine, and ejection fraction/modified age, creatinine, and ejection fraction scores (37,38); the Clinical SXscore (39,40); and the additive/logistic EuroSCOREs (22,23)-a brief description of which is enclosed in the Online Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Results demonstrated that R-ZES was noninferior to EES with respect to the 12-month primary clinical endpoint of target lesion failure (TLF) (R-ZES 8.2% vs. EES 8.3%, p noninferiority Ͻ 0.001), a composite of cardiac death, target-vessel myocardial infarction (MI), and clinically driven target lesion revascularization (TLR) and the 13-month secondary angiographic endpoint of in-stent diameter stenosis (R-ZES 21.65 Ϯ 14.42% vs. EES 19.76 Ϯ 14.64%, p noninferiority ϭ 0.035). In this sub-study of the RESOLUTE All Comers trial the prognostic value of the SXscore was assessed in isolation and in comparison with the Age, Creatinine and Ejection Fraction (ACEF score) (14,15) and the clinical SYNTAX score (CSS), (16) in an all-comers population treated with second-generation DES.…”
mentioning
confidence: 99%